(untitled) (Web of Technology: Multidimensional Research Journal, 2024)
In this article, when teaching students the topic of predicting yields using dynamic series of mathematics, the support of theoretical data directly on the solution of Agricultural Issues is studied using pedagogical experiments, which leads students to better master science, strengthen their professional training.